Optimalisasi Peran Gerakan Pemuda Ansor Pimpinan Wilayah Dki Jakarta Dalam Upaya Pencegahan Radikalisme - Zakaria, Akbar; Widodo, Pujo; Kertopati, Susaningtyas Nefo H; Firdaus, Mochammad Ferdion (Prodi Sosiologi FISIP Universitas Teuku Umar, 2024)
The National Counterterrorism Agency stated that there had been a decrease in terrorism cases by 89% in the last five years. Even though it is quite significant, efforts to prevent terrorism, especially preventing radicalism, must still be carried out. This is because there are indications of a change in approach from violence to a softer one. One area that needs special attention regarding the development of radicalism is Jakarta Province. The 2022 Radicalism Potential Index states that radicalism in DKI Jakarta has high potential. Efforts to strengthen the prevention of radicalism in Jakarta require massive community participation. This article discusses optimizing the role of the Jakarta Regional Leadership Ansor Youth Movement (GP Ansor) as a religion-based youth organization in preventing radicalism. The GP Ansor organization is a non-profit, religious-based youth organization that has adequate potential and resources to counter the development of radicalism. The method used in this paper is qualitative research in the nature of a literature study. The study begins with searching and collecting library sources, processing data and information, analyzing and drawing conclusions. The results of the study show that there is an important role for the GP Ansor organization in preventing radicalism in Jakarta. This role needs to be optimized so that it can increase community participation in preventing radicalism in Jakarta. Optimization is carried out through improvements in several aspects of the organization which include facilities and infrastructure, budget and human resources.